Close intimate playthings? Understanding player-avatar relationships as a function of attachment, agency, and intimacy - Banks, Jaime; Bowman, Nicholas David (AoIR Selected Papers of Internet Research, 2013)
The study of the player-avatar relationship has been central to scholars of video games and virtual worlds. Work has attempted to explain the relationship by focusing on the technologies of social presence, the socio-emotional relationship between players and avatars as distinct social others, the capability of players to adopt the personae of their avatars, and the psychological merging of player and avatar as a unified person. While these approaches are useful in explaining specific forms and types of player-avatar relationships, they tend to adopt qualitatively-different approaches to the phenomenon that limit their ability to inform one another and, in turn, our understanding of the holistic player-avatar experience. To this end, the following paper demonstrates how player-avatar archetypes generated from narrative analysis can be reanalyzed for dimensions of character attachment to highlight intersections with agency and intimacy, and suggests the utility of such an approach to understanding the larger video game entertainment experience.